2019
DOI: 10.1021/acs.orglett.8b04120
|View full text |Cite
|
Sign up to set email alerts
|

Direct C4-Benzylation of Indoles via Tandem Benzyl Claisen/Cope Rearrangements

Abstract: A novel direct C4 benzylation of indoles utilizing 2-benzyloxyindoles has been developed to access 4-benzyl-2-oxindoles. This strategy involves the in situ formation of isotoluene intermediates via benzyl Claisen rearrangements, which undergoes Cope rearrangement and aromatization. The method provides the desired products in moderate to high yields and shows good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We planned to apply our reported haloetherification methods to 2,2-disubstituted morpholine analogues 17 and 4-benzyloxyindoles. 18…”
Section: Letter Synlettmentioning
confidence: 99%
“…We planned to apply our reported haloetherification methods to 2,2-disubstituted morpholine analogues 17 and 4-benzyloxyindoles. 18…”
Section: Letter Synlettmentioning
confidence: 99%
“…have developed a direct C4 benzylation of indoles utilizing 2-benzyloxyindoles, affording 4-benzyl-2-oxindoles (Scheme 1C). 11 This reaction involves the formation of isotoluene intermediates in situ via a benzyl Claisen rearrangement, which undergo Cope rearrangement and aromatization (Scheme 1C, path b). In these investigations, we concluded that the initially expected isochromeno[3, 4-b]indoles could not be obtained through the isotoluene intermediate followed by cyclization (Scheme 1C, path a).…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…Initially, the reaction was carried out using N-Ts 2-benzyloxy-3-bromoindoline (1aa) 11 and 5 equiv of Ag 2 O in EtO-Ac at room temperature. As expected, the reaction proceeded smoothly to afford isochromeno[3,4-b]indoline 2aa in 62% yield (Table 1, entry 1).…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…8 Hence, the development of a practical and general method for the selective synthesis of substituted oxindole, which will minimize the number of steps and increases complexity and diversity, is an attractive subject in organic synthesis. 9 On the other hand, diazocarbonyl compounds, a vital coupling partner in organic synthesis for the construction of various complex molecule, 10 in the presence of metal catalyst generates important reactive intermediate, viz., metal carbeniods. This intermediate undergoes various useful transformations including insertion into C-H 11 and X-H/C bond, 12 ylide generation-cum-functionalization, 13 etc.…”
Section: Introductionmentioning
confidence: 99%